Campus Wide Healthy Eating Initiative - Mortensen, Amanda (My University, 2012)
College and universities are excellent settings to encourage healthy eating through educational programming and delivery of healthier foods and dining options. Such settings could also encourage healthy eating among faculty and staff, yet most healthy eating studies focus only on students. The aims of this study were to examine similarities and differences among groups to inform the development of policy and environmental changes that target the needs and circumstances of all campus members.
Color poster with text, images, graphs, and tables.
Keywords: College students--Health and hygiene; College students--Nutrition; Universities and colleges--Employees--Health and hygiene; Universities and colleges--Employees--Nutrition; Posters